v.2 - All India Congress Committee (New Delhi, 1985)
The second volume of the Centenary History touches upon the transformation of the Congress into a party of the people under the aegis of Mahatma Gandhi. This volume also deals with the dissemination of socialist ideas within the national movement through the initiative of Jawaharlal Nehru.
Keywords: Political Parties-India